Telework uncovered: Employees' perceptions across various occupations in an industrial company - Tea Korkeakunnas; Malin Lohela Karlsson; Marina Heiden; Komalsingh Rambaree (Administrative Sciences, 2025)
To understand how telework is perceived among occupational groups with different work tasks within the same company, this qualitative study aimed to explore how managers and employees experience telework in relation to well-being, individual performance, and the work environment. This qualitative study used a phenomenographic approach. Fourteen online interviews, comprising seven managers and seven employees from the same industrial company, were conducted between February 2022 and September 2023. The data were analyzed inductively to capture variations in telework perceptions. The findings showed that telework is not universally beneficial or challenging; its effectiveness depends on contextual factors such as team setting, job role, type of work, and organizational culture. Telework benefits both employees and managers engaged in individual tasks (e.g., reading, drafting contracts, and preparing reports) or global collaborations, including improved well-being, work-life balance, and overall performance. However, starting with an office-based period that facilitated team cohesion, faster learning, and a deeper understanding of the organizational culture. Face-to-face onsite work could be time-consuming and, therefore, stressful for some, but it is time-saving for others. Onsite employees and managers faced increased workloads when colleagues teleworked, as employees tended to rely more on colleagues physically present in the office. This research highlights the need for tailored strategies to enhance the advantages of telework while reducing its challenges. It contributes to existing research by providing nuanced insights into the relationship between telework and occupational groups within an industrial setting and offering practical guidance for telework in this field.
Keywords: 350; flexible work; organization; performance; phenomenographic research; remote work; telecommute; work environment; work task